If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34 + -6x = 5 Solving 34 + -6x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-34' to each side of the equation. 34 + -34 + -6x = 5 + -34 Combine like terms: 34 + -34 = 0 0 + -6x = 5 + -34 -6x = 5 + -34 Combine like terms: 5 + -34 = -29 -6x = -29 Divide each side by '-6'. x = 4.833333333 Simplifying x = 4.833333333
| 6+y=-44 | | (v+3)/(v^2-3v-40) | | 5y+6y=y+10 | | 5/3x+3+23 | | 4.5+x=0.5 | | 6(-8)+y=-44 | | 3(x+6)+2(x-2)=6 | | b/3-12=8 | | X^9+125x^6=0 | | 12x-144=4x-8 | | 13n-6-12n+9=12 | | y/8+10=16 | | 12=5+11c-2 | | x+(2x-4)+(x+5)+2x+6=10x | | -8x+5x-6=-2x | | 0.4n+6=8 | | 0.4+6=8 | | 0.4x+6=8 | | 9(k-6)-(8k-6)=3 | | x+(2x-4)+(x+5)+2x+6=10 | | 3x-7-11x=44 | | 10+3x=2x+15 | | 3x^2=x^2 | | 4x-5=28x+13 | | 12x=6x+5 | | 3(x-2)=7x | | 2x+3=-5x+5/2 | | 15x-5=27x+3 | | 75-7x=38x+15 | | 15+8a=39 | | -2(t-4)+7t=9t-1 | | 2(Y+1)=1(3Y) |